1998
DOI: 10.3109/08923979809038545
|View full text |Cite
|
Sign up to set email alerts
|

Taraxacum OfficinaleRestores Inhibition of Nitric Oxide Production by Cadmium in Mouse Peritoneal Macrophages

Abstract: Nitric oxide (NO) produced at high concentrations by the inducible NO synthase is an important effector molecule involved in immune regulation and defense. The involvement of NO in the toxicity of cadmium (Cd) has been proposed. We have established that Cd inhibits the production of NO by recombinant IFN-gamma (rIFN-gamma) and lipopolysaccharide-stimulated mouse peritoneal macrophages. In the present study, we searched restoration drug against the inhibition of NO production by Cd in Oriental medicine. An aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…110,137,138 There are also herbal extracts/drugs that enhance the production of NO via iNOS. These drugs [148][149][150][151][152] are generally used as anticancer and antibacterial folk remedies. A classic example is the development of the antineoplastic agent paclitaxel (Taxol; Bristol Myers Squibb, New York, NY, USA) from the dried bark or leaf of Taxus chinesis or Taxus yunnanensis.…”
Section: Plants As Medicine: Traditional Chinese Herbal Medicinementioning
confidence: 99%
“…110,137,138 There are also herbal extracts/drugs that enhance the production of NO via iNOS. These drugs [148][149][150][151][152] are generally used as anticancer and antibacterial folk remedies. A classic example is the development of the antineoplastic agent paclitaxel (Taxol; Bristol Myers Squibb, New York, NY, USA) from the dried bark or leaf of Taxus chinesis or Taxus yunnanensis.…”
Section: Plants As Medicine: Traditional Chinese Herbal Medicinementioning
confidence: 99%
“…Our Cd intoxication in drinking water (100 mg CdCl 2 /l) increased the superoxide production throughout the experiment. This could correspond to the results obtained by Kim et al (1998), who observed stimulation of IFN- production, an important activator of macrophage's energetic system (Schroder et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
“…As in Figure 2, rate of WBC in groups 1 (treated with dose of 50 mg/kg), 2 (treated with dose of 100 mg /kg), and 3 (treated with dose of 200 mg/kg) than the control group has increased, but these differences only in group 3 are significant, and as the Figure 3 indicated that rate of lymphocyte in these experimental groups 1, 2, 3 than the control group has increased significantly. The reason of this increasing is due to anti-virus effects [14], antiinflammatory effects [15] and antibacterial effects [16] of this plant. According to Singh study and colleagues in 2008, phenolic compounds in dandelion such as chicoric acid inhibit the penetration of viruses in cells.…”
Section: Resultsmentioning
confidence: 99%